TWO STRATEGIES FOR STUDYING DIALOGUE IN UKRAINIAN PSYCHOLOGY (Pedagogy of Higher and Secondary Education, 2022)
In the article two strateges of research of dialogue open up in Ukranian psychology.
Keywords: dialogue; dialogic approach-genetis strategy; development and self development of personality